Students emotions in the ELT classroom - Ortega Cediel, German Andres; Paez Suarez, Luis Camilo (Corporación Universitaria Minuto de Dios, 2015)
During our practice and observations carried out in Colegio Técnico y Académico Celestin Freinet, we were able to identify the difficulties that the students encounter at the moment of presenting an oral production activity in front of the class, reducing the amount of speaking and the quality of it, making more difficult for the students and the teacher to share their ideas, increasing the frustration that the students might feel. This proposal emerged after the experience that one of the researchers had in a previous school in which some of the students from tenth grade felt overwhelmed by their emotions and were not able to complete their oral presentations in front of the class. The students let the teachers know that fear and shame were behind the way they felt and how the previously mentioned emotions and feelings prevented them from speaking in front of the class.
Keywords: Classrrom; Producing language; LENGUAJE Y LENGUAS; PEDAGOGÍA; MÉTODOS DE ENSEÑANZA; EMOCIONES